G82S polymorphism of receptor for advanced glycation end products gene and serum soluble RAGE levels in mild cognitive impairment and dementia of Alzheimer's type patients in Turkish population. (January 2019) - Ataç, Zehra Simin; Alaylıoğlu, Merve; Dursun, Erdinç; Gezen-Ak, Duygu; Yılmazer, Selma; Gürvit, Hakan
Highlights: 82S allele was suggested to be associated with increased risk of AD. Circulating sRAGE collects peripheral Aβ, prevents transfer of Aβ into brain. An association between RAGE G82S polymorphism and sRAGE levels was shown. Circulating sRAGE concentration is reported to decrease in AD case. Although it's not significant, highest mean sRAGE level is found in DAT in our study. We observed that A allele attenuates serum sRAGE levels but no significant correlation. Abstract: Alzheimer's disease (AD) is a chronic, neurodegenaration resulting in progressive cognitive decline leading to dementia. Mild cognitive impairment (MCI) is also a clinical definition of cognitive decline without functional impairment. Receptor for advanced glycation end products (RAGE) is one of the neuronal membrane receptors that binds amyloid beta peptide (Aβ) triggering Aβ-related pathologic signalling mechanisms. Soluble RAGE (sRAGE) is the soluble isoform of RAGE and it collects peripheral Aβ by acting as a sink, prevents both RAGE-AGE interaction and transfer of Aβ into brain. In this study, an association was investigated in Turkish cohorts of patients with dementia with Alzheimer's Type (DAT) and MCI patients by measuring serum sRAGE levels and by genotyping G82S polymorphism and comparing them to healthy control (HC) subjects. Although the serum sRAGE levels showed a decreasing manner among the groups, these differences were not statistically significant (p = 0.2). This is the first study for Turkish population.